A Selective Small‐Molecule c‐Myc Degrader Potently Regresses Lethal c‐Myc Overexpressing Tumors. Issue 8 (20th January 2022) - Xu, Ying; Yu, Qingfeng; Wang, Ping; Wu, Zhaoxing; Zhang, Lei; Wu, Shuigao; Li, Mengyuan; Wu, Bowen; Li, Hongzhi; Zhuang, Haifeng; Zhang, Xuzhao; Huang, Yu; et al.
Abstract: MYC oncogene is involved in the majority of human cancers and is often associated with poor outcomes, rendering it an extraordinarily desirable target, but therapeutic targeting of c‐Myc protein has been a challenge for >30 years. Here, WBC100, a novel oral active molecule glue that selectively degrades c‐Myc protein over other proteins and potently kills c‐Myc overexpressing cancer cells is reported. WBC100 targets the nuclear localization signal 1 (NLS1)–Basic–nuclear localization signal 2 (NLS2) region of c‐Myc and induces c‐Myc protein degradation through ubiquitin E3 ligase CHIP mediated 26S proteasome pathway, leading to apoptosis of cancer cells. In vivo, WBC100 potently regresses multiple lethal c‐Myc overexpressing tumors such as acute myeloid leukemia, pancreatic, and gastric cancers with good tolerability in multiple xenograft mouse models. Identification of the NLS1–Basic–NLS2 region as a druggable pocket for targeting the "undruggable" c‐Myc protein and that single‐agent WBC100 potently regresses c‐Myc overexpressing tumors through selective c‐Myc proteolysis opens new perspectives for pharmacologically intervening c‐Myc in human cancers. Abstract : This study identifies the NLS1–Basic–NLS2 domain as a druggable pocket for directly targeting c‐Myc protein. As a novel potent and selective c‐Myc inhibitor, WBC100 directly targets nuclear c‐Myc and E3 ligase CHIP for proteasome‐dependent degradation. Importantly, WBC100 regresses c‐Myc overexpressing acute myeloid leukemia, pancreatic, and gastric cancers in mouse models.